A Case of Hemophagocytic Syndrome due to Tuberculosis: Uncommon Manifestation of a Common Disease. (27th October 2014) - Singha, Arijit; Mukherjee, Adreesh; Dasgupta, Riddhi; Das, Tapas
Abstract : Hemophagocytic syndrome, also known as hemophagocytic lymphohistiocytosis (HLH), is the manifestation of immune dysregulation. It is associated with ineffective but exaggerated immune response and infiltration of active lymphocytes and histiocytes in various organs. This devastating clinical condition has myriad of clinical and biochemical manifestations such as fever, splenomegaly, pancytopenia, hypertrygliceridemia, and hyperferritinemia. It can be either primary or secondary. Primary HLH usually presents in childhood. Secondary HLH occurs due to infection mostly viruses but other aetiologies are also important as early detection and treatment may improve survival. Hemophagocytosis due to tuberculosis is uncommon. Only handful of cases have been reported mostly in immunocompromised patients. We report a case of hemophagocytic syndrome associated with disseminated tuberculosis in an immunocompetent women highlighting early diagnosis and treatment is a demanding need in this devastating disease.